COMPETENCY OF PROVINCIAL ADMINISTRATIVE ORGANIZATIONS IN THE EASTERN REGION IN PROVIDING EDUCATION FOR PERSONS WITH DISABILITIES - Puripanik, Teerapong (Journal of MCU Nakhondhat, 2025)
This article has the objective to study 1) The core competency management of the Provincial Administrative Organization in the Eastern Region in providing education for persons with disabilities; 2) The factors correlated with the competency of the Provincial Administrative Organization in the Eastern Region in providing education for persons with disabilities; 3) The problems and limitations in developing the competencies of the Provincial Administrative Organization in the Eastern Region in providing education for persons with disabilities. The research combines mixed methods: Quantitative and qualitative. The sample group consists of educators, e.g. teachers working in schools under the supervision of the Provincial Administrative Organization in the Eastern Region, totaling 317 people. The research tools include questionnaires and descriptive statistics analysis, such as percentage, mean, deviation and inference statistics, e.g. t-test, one-way Anova, Linear Coefficient Correlation and Multiple Regression Analysis. The research result has shown that 1) The core competency of the Eastern Region Provincial Administrative Organization in providing education for persons with disabilities is overall at a high level ( = 3.88) and the competency in system management is also at a high level ( = 3.68); 2) The analysis of t-test and one-way ANOVA reveals that the highest educational level and knowledge of inclusive education are significant factors affecting the competency of the Eastern Region Provincial Administrative Organization in providing education for persons with disabilities and 3) The core competency of educational personnel in the Eastern Region Provincial Administrative Organization shows a moderate correlation (r = 444) with the competency of these organization in providing education for persons with disabilities with statistical significance at the .05 level.